The ERS Research Agency: the beginning. Issue 4 (April 2016) - Soriano, Joan B.; Paton, James; Martin Burrieza, Fernando; Bill, Werner; Pannetier, Carine; Aliberti, Stefano; Adcock, Ian M.; Wagers, Scott; Migliori, Giovanni Battista
The modern research environment is much more complex and challenging than before [1]. Mechanistic research has become increasingly sophisticated and specialised, while new clinical research approaches have vastly increased the amount of data generated. These new developments bring a number of challenges. As part of its 2013–2018 strategic plan, the European Respiratory Society launches the ERS Research Agency http://ow.ly/WZyac